2000
DOI: 10.1002/1096-8628(20001002)94:4<281::aid-ajmg3>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Ablepharon-Macrostomia syndrome: First report of familial occurrence

Abstract: Ablepharon-macrostomia syndrome (AMS) is a rare condition comprising severe deficiency of the anterior lamella of both eyelids, abnormal ears, macrostomia, anomalous genitalia, redundant skin, and absence of lanugo. There is no agreement about cause; some authors suggest autosomal recessive inheritance. We describe familial occurrence of AMS in a girl, sister of a previously reported patient. The father has facial anomalies that suggest autosomal dominant inheritance. Am. J. Med. Genet. 94:281-283, 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 11 publications
3
35
1
8
Order By: Relevance
“…5,6,11,19,20,24 BSS is characterized by The American Journal of Human Genetics 97, 1-12, July 2, 2015 3 ectropion, macrostomia, ear abnormalities, bulbous nose with hypoplastic alae nasi, redundant skin, hypertrichosis, and variable other features. 14,16,21,23,25,26 Several instances of parent-to-child transmission suggest that both AMS and BSS are inherited in an autosomal-dominant fashion, 2,8,9,21,22 but no specific gene defect has been associated with these disorders. The substantial phenotypic overlap between AMS and BSS, as well as a shared mode of inheritance, supports the hypothesis that the two disorders are caused by dominant mutations in the same gene.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,11,19,20,24 BSS is characterized by The American Journal of Human Genetics 97, 1-12, July 2, 2015 3 ectropion, macrostomia, ear abnormalities, bulbous nose with hypoplastic alae nasi, redundant skin, hypertrichosis, and variable other features. 14,16,21,23,25,26 Several instances of parent-to-child transmission suggest that both AMS and BSS are inherited in an autosomal-dominant fashion, 2,8,9,21,22 but no specific gene defect has been associated with these disorders. The substantial phenotypic overlap between AMS and BSS, as well as a shared mode of inheritance, supports the hypothesis that the two disorders are caused by dominant mutations in the same gene.…”
Section: Introductionmentioning
confidence: 99%
“…Nine previously published patients from eight unrelated families [Price et al, ; Cruz et al, ; Ferraz et al, ; Stevens and Sargent, ; Brancati et al, ; Kallish et al, ] and two unpublished cases with AMS could be recruited for this study. The two novel patients represented sporadic cases born to unrelated parents with an unremarkable family history, and they exhibited typical signs of this syndrome.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Nevertheless, the nature of facial, particularly ocular anomalies and associated renal and laryngotracheal malformations usually allow to distinguish FS from AMS. Fourteen well‐documented cases of AMS have been described in the literature [McCarthy and West, ; Hornblass and Reifler, ; Jackson et al, ; Price et al, ; Cruz et al, ; Ferraz et al, ; Stevens and Sargent, ; Brancati et al, ; Kallish et al, ; Rohena et al, ]. In three possible further cases, the diagnosis is less clear [Pellegrino et al, ; Amor and Savarirayan, ; Cavalcanti et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMS has been reported to be an autosomal recessive entity, and it has been suggested that the gene maps to 18q [1]. Cruz et al [2] described affected siblings, and Ferraz [3] reported a familial case which affected father and son.…”
Section: Introductionmentioning
confidence: 99%